UPAYA MENINGKATKAN PRESTASI BELAJAR PKn MELALUI METODE PEMBELAJARAN KOOPERATIF MODEL STAD (STUDENT TEAMS ACHIEVEMENT DIVISION) - Mishbakhuddin Mishbakhuddin (MEDIA DIDAKTIKA, 2019)
This study aims to describe (1) increasing PKn learning achievement and (2) the influence of PKn learning motivation after the implementation of cooperative learning in the STAD model. This action research was carried out in three cycles and used a tool to collect teacher-made test data and observation sheets. The research subjects were students of class VI Semester II at Moro Elementary School. The results showed that the cooperative learning method of the STAD model could improve the quality of PKn learning. The STAD model cooperative learning method has a positive impact on increasing student learning prestige which is characterized by an increase in student learning completeness in each cycle, namely the first cycle (68.42%), cycle II (81.58%), cycle III (94.74% ).